Pengembangan Dadih Sebagai Pangan Fungsional Hasil Fermentasi Berbagai Kultur Starter Lactobacillus Indigenus - Puspawati, Ni Nyoman; Indri Hapsari Arihantana, Ni Made; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p16, 2023)
Fermented milk is milk that is fermented by lactic acid bacteria. Fermented milk containing live lactic acid bacteria is very good for the health of the digestive system. One example of a very well-known fermented milk product is dadih. Dadih is a traditional Minangkabau yogurt made from buffalo milk. Dadih is made traditionally and there is no standard manufacturing process, so the quality of dadih varies in terms of taste, aroma and texture. Traditional production of dadih without starter causes the consistency of taste, aroma and texture to be difficult to maintain. The controlled fermentation process in the manufacture of dadih uses probiotic bacteria so that it has the opportunity to be developed as a functional food. The purpose of this study was to determine the potential of Indigenous Lactobacillus isolated from bamboo as a starter culture in the development of dadih as a functional food. Lactobacillus isolates used in this study were isolates ML7, MR2, RL2, RL4, RM1 and RN9. The results showed that the use of various types of Lactobacillus isolates had a very significant effect (P>0.01) on yield, moisture content, ash content, protein content, pH, total acid, total LAB and sensory evaluation of the dadih produced. The use of Lactobacillus RN9 isolate as a starter culture produced the best dadih with yield characteristics of 78.33%, moisture content 78.94%, ash content 1.09%, protein content 6.74%, pH 4.75, total titrated acid 0.56 %, total LAB 8.70 log CFU/g and yellowish white color typical of milk, slightly sour milk aroma, savory like cheese aroma, sour milk taste and no bitter aftertaste, soft to slightly hard texture, soft and compact or not sandy.